2019
DOI: 10.1038/s41467-019-10669-0
|View full text |Cite
|
Sign up to set email alerts
|

m6A mRNA demethylase FTO regulates melanoma tumorigenicity and response to anti-PD-1 blockade

Abstract: Melanoma is one of the most deadly and therapy-resistant cancers. Here we show that N 6 -methyladenosine (m 6 A) mRNA demethylation by fat mass and obesity-associated protein (FTO) increases melanoma growth and decreases response to anti-PD-1 blockade immunotherapy. FTO level is increased in human melanoma and enhances melanoma tumorigenesis in mice. FTO is induced by metabolic starvation stress through the autophagy and NF-κB pathway. Knockdown of FTO increases m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
531
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(548 citation statements)
references
References 52 publications
8
531
1
8
Order By: Relevance
“…In melanoma, FTO impairs IFNγ-induced killing in melanoma cells in vitro via up-regulating PD-1, CXCR4, and SOX10 through suppressing YTHDF2-mediateddegradation and inhibits response to anti-PD-1 blockade immunotherapy [69].…”
Section: Ftomentioning
confidence: 99%
“…In melanoma, FTO impairs IFNγ-induced killing in melanoma cells in vitro via up-regulating PD-1, CXCR4, and SOX10 through suppressing YTHDF2-mediateddegradation and inhibits response to anti-PD-1 blockade immunotherapy [69].…”
Section: Ftomentioning
confidence: 99%
“…By targeting PD1 in cytotoxic T cells or PD-L1 in cancer cells, immune checkpoint therapies activate the adaptive immune system to eliminate cancer cells. Yang et al showed that knockdown of FTO sensitizes melanoma cells to interferon gamma and anti-PD1 treatments [95]. m6A modification is also implicated in the neoantigen-specific T cell immune response.…”
Section: Diagnosis and Therapeutic Potentialmentioning
confidence: 99%
“…In melanoma, depletion of YTHDF2 accelerated cell proliferation and migration by strikingly upregulating the mRNA levels of three key intrinsic pro-tumorigenic factors, including PD-1 (PDCD1), CXCR4, and SOX10, which was dependent on a reduced m 6 A-mediated mRNA decay [64]. Furthermore, YTHDF1 promoted the translation of tumor suppressor HINT2 mRNA which was methylated by m 6 A, thus playing a repressive role in ocular melanoma [65].…”
Section: Melanomamentioning
confidence: 99%
“…Downregulating the mRNA and protein levels of three key intrinsic pro-tumorigenic factors, including PD-1 (PDCD1), CXCR4 and SOX10 [64] YTHDF1 HINT2 Promoting the translation of HINT2 mRNA [65] Breast cancer YTHDF2 BNIP3 Facilitating the degradation of BNIP3 mRNA [66] Pancreatic cancer IGF2BP2 DANCR Enhancing the DANCR expression [67] Acute myeloid leukemia…”
Section: Itga6mentioning
confidence: 99%